CHICKLIT MOVIES: An Attempt of Showing Identity or Looking for Identity ? A Case Study on Bridget Joneâs Diary, Confession of Shopaholic And Devil Wears Prada - Dinurriyah, Itsna (Pusat Studi Gender dan Anak LPPM UIN Sunan Ampel Surabaya, 2013)
Chick lit is a modern literature that achieves its success since the presence of Bridget Joneâs Diary in anewspaper in the UK. Originally, the story is underestimated but extremely affecting many metropolitanwomen in the UK at the time. The influence and the fever spread throughout the world, especially America.Eventually, many chick lit piece of work become a great success and offer help to provide the identity forwoman who live in big cities; those who are successful, fashionable, independent and single. This success alsois supported by a rapid response from the film industry to sell the chick lit as the theme in their movies.Admittedly, these so called literary works that can be finished in one read are packed so enjoyable andentertaining. Yet, the question then appears when there is a shifting way and process of the metropolitanwomen in seeking their indentity.